Sugarcane bagasse-based adsorbent as an alternative to enhance the harvesting process of Chlorella vulgaris biomass - Basri, W.N.F.W. (Penerbit Akademia Baru, 2018)
This research brightens a new approach to enhance Chlorella vulgaris biomass harvesting process using low-cost sugarcane bagasse-derived adsorbents in the optimized culture medium. Sugarcane bagasse-derived adsorbents were activated using different chemical concentration. Acid modified sugarcane bagasse-derived adsorbents of 1.5 M resulted the highest adsorption capacity of 66. Point of zero charge was carried out the explained the reasons. The samples viewed under SEM showed 1.5M acid modified sugarcane bagasse-derived adsorbents have highest microalgae adsorption. Different sizes (710Î¼m, 1mm, 2mm and 4mm) of 1.5M acid modified sugarcane bagasse-derived adsorbents were tested and 4mm-sized sugarcane bagasse-derived adsorbents gave the best adsorption. Â© 2016 Penerbit Akademia Baru.